Development of COVID-19 Case in District and City of Jambi Province with Exponential Smoothing Methode - Sherli Yurinanda; Cut Multahadah; Reni Aryani (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2020)
Jambi Province is one of the province in western Indonesia, which was affected by COVID-19 in March and until mid-September the number confirmed positive reached 345 people. Until now COVID-19 has become a pandemic.Based on this data, it is necessary to predict the number of COVID-19 in Jambi Province, including every district in Jambi city. Double exponential smoothing: The Holt two-parameter method determines the value of the trend with a tang parameter different from the parameter used in the original series. The principle of forecasting using multiple exponential smoothing: The Holt two-parameter method uses two smoothing constants with values between 0 and 1. Based on the results of forecasting using the double exponential smoothing by Holt method, it can be seen that the number of confirmed cases of Covid-19 in each region in Jambi Province continues to increase. This case is estimated to increase to 352 people in mid-October.